Analisis Efisiensi Pengopenan Transformator Distribusi di PT Power Services - M Aldi Firmansyah; Aripin; Linda Faridah (PT. Hasba Edukasi Mandiri, 2026)
This Distribution transformers are essential devices in electrical networks, transferring power from transmission lines to consumers at usable voltage levels. Their reliability is closely linked to the condition of the insulation system, primarily composed of mineral oil and cellulose paper, which are highly sensitive to moisture. To reduce water absorption, an oven drying process is applied, improving both insulation resistance and oil breakdown voltage. This study investigates the efficiency of the oven drying process at PT Harifff Power Services using a case study approach. Data were collected through direct observation, insulation resistance testing, oil breakdown voltage measurement, and interviews with field technicians. Findings reveal that the drying process took between 7 and 14 days, significantly longer than the 1–2 days recommended in literature at 100–120 °C. The main limitation is the absence of an automatic temperature control system in the vacuum oven, leading to inefficiency. Nevertheless, post-drying measurements indicate improved insulation quality. It is therefore recommended to upgrade the oven with temperature control and to optimize storage procedures to achieve greater efficiency and extend the lifespan of distribution transformers.